2022
DOI: 10.1186/s40364-022-00374-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune cells-derived exosomes function as a double-edged sword: role in disease progression and their therapeutic applications

Abstract: Exosomes, ranging in size from 30 to 150 nm as identified initially via electron microscopy in 1946, are one of the extracellular vesicles (EVs) produced by many cells and have been the subject of many studies; initially, they were considered as cell wastes with the belief that cells produced exosomes to maintain homeostasis. Nowadays, it has been found that EVs secreted by different cells play a vital role in cellular communication and are usually secreted in both physiological and pathological conditions. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 206 publications
0
49
0
Order By: Relevance
“…The presence of mitochondrial, centrosomal, and ribosomal proteins on MVs suggests their roles in protein translation. In addition, microglial exosomes are involved in antigen presentation, such as the transfer of antigens, indicating a functional role in immune response and are essential for regulating the brain-immune system interaction ( Kalluri and LeBleu, 2020 ; Guo et al, 2021 ; Hazrati et al, 2022 ). Studies have revealed that neurodegenerative disease-related proteins are transported by microglial exosomes.…”
Section: Microglia and Its Interaction With Brain Cellsmentioning
confidence: 99%
“…The presence of mitochondrial, centrosomal, and ribosomal proteins on MVs suggests their roles in protein translation. In addition, microglial exosomes are involved in antigen presentation, such as the transfer of antigens, indicating a functional role in immune response and are essential for regulating the brain-immune system interaction ( Kalluri and LeBleu, 2020 ; Guo et al, 2021 ; Hazrati et al, 2022 ). Studies have revealed that neurodegenerative disease-related proteins are transported by microglial exosomes.…”
Section: Microglia and Its Interaction With Brain Cellsmentioning
confidence: 99%
“…In this study, it is shown that PBMCs that were infected and uninfected with H. pylori secrete exosomes, however, the methods that were used make it impossible to demonstrate whether there are differences in the number of exosomes that are secreted. PBMCs including NK cells, dendritic cells, macrophages, mast cells, B lymphocytes, and T lymphocytes can secrete exosomes [ 50 , 51 , 52 , 53 , 54 ]. Previous studies show that exosomes are related to the development of gastrointestinal diseases such as chronic gastritis and gastric cancer, and also to the progression to extra-gastrointestinal diseases, including atherosclerosis [ 17 , 18 , 19 , 20 , 21 , 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…responses (20). Therefore, a large number of researches have used immune cells-derived Exos as drug carriers for cancer immunotherapy.…”
Section: Immune Cells-derived Exosmentioning
confidence: 99%